Method for preparing magnetic coal gasification slag composite material through mechanochemical method and application of magnetic coal gasification slag composite material
Magnetic coal gas slag composite materials were prepared by mechanochemical method, which solved the problem of coal gas slag and phenol-containing wastewater treatment, achieved resource recycling and reduction of environmental pollution, and achieved efficiency of 99-100%.
Patent Information
- Application Number
- CN202411975893.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The problem of handling coal gasification slag and phenol-containing wastewater leads to environmental pollution and waste of resources, and lacks effective resource utilization technology.
Through mechanochemical method, mineral particles in the coal gasification slag are broken, active metal is exposed, and complexing agent is used to promote the migration of metal to the surface, forming a magnetic coal gasification slag composite material, improving its catalytic activity against persulfate and enhancing the removal efficiency of phenolic pollutants in water.
The resource utilization of coal gasification slag has been achieved, the harm of solid waste and phenol-containing wastewater to the environment has been reduced, and the purpose of waste control is achieved, and the resource recycling efficiency has reached 99-100%.
Smart Images

Figure CN119793461A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycling of solid waste resources, and in particular to a method for preparing a magnetic coal gasification slag composite material by a mechanochemical method and application thereof. Background Art
[0002] The coal-based energy structure has led to the development of comprehensive coal utilization technologies in China, injecting lasting impetus into infrastructure and economic development. However, with the rapid development of the coal industry, water shortage, carbon emissions, and solid waste accumulation have become increasingly prominent. Among them, the large-scale accumulation of coal-based solid waste, especially coal gasification slag, has gradually attracted attention.
[0003] Coal gasification technology is one of the important ways to achieve efficient and clean utilization of coal. It is the leader of the current coal chemical industry and provides synthesis gas for the entire back-end chemical production. However, a large amount of coal gasification slag is inevitably produced in the process. my country converts nearly 250 million tons of raw coal through coal gasification each year, and the annual emission of coal gasification slag exceeds 33 million tons. However, due to the lack of suitable resource utilization technology and processing equipment, a large amount of coal gasification slag cannot be quickly and completely consumed, and can only be piled up and landfilled, which not only occupies a large amount of land resources, but also causes serious harm to the environment. Related issues have seriously restricted the rapid development of local enterprises and have become an important issue that needs to be urgently resolved in the process of clean production.
[0004] In addition, phenol-containing wastewater is a common type of organic wastewater in industrial production processes. It has strong biological toxicity, complex components, and is difficult to treat. In the current water pollution control, phenol-containing wastewater has been clearly listed as one of the harmful wastewaters that need to be tackled and solved due to its serious harm to the ecological environment and human health. It is urgent to develop more efficient and feasible treatment technologies and processes.
[0005] Therefore, it is urgently necessary to develop gasification slag-based composite materials with simple preparation processes to achieve the coordinated and parallel goals of solid waste reduction, resource utilization and harmlessness, and apply them to the treatment of phenol-containing wastewater to reduce the harm of solid waste and phenol-containing wastewater to the environment, achieve the purpose of treating waste with waste, and realize resource recycling. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a magnetic coal gasification slag composite material by a mechanochemical method and its application. The coal gasification slag is used as a raw material, and the mineral particles in the coal gasification slag are crushed by mechanical ball milling to promote the rapid exposure of active metals wrapped by minerals in the coal gasification slag, and a chelating agent is used to quickly pull the exposed metals to the surface of the coal gasification slag minerals or residual carbon, thereby realizing the migration and transformation of the metal from the inside to the outside, improving the catalytic activity of the composite material for permonosulfate (PMS), and enhancing the removal efficiency of phenol pollutants in water, thereby achieving the purpose of treating waste with waste.
[0007] The present invention provides a method for preparing a magnetic coal gasification slag composite material by a mechanochemical method, comprising the following steps:
[0008] (1) a certain mass of coal gasification slag is loaded into a ball milling tank of a high energy ball mill together with grinding balls according to a certain ball-to-material mass ratio, and ball milled at a speed of 2000 r / min for a certain period of time to obtain ball-milled coal gasification slag with exposed metal;
[0009] (2) adding the complexing agent and the ball-milled coal gasification slag obtained in step (1) to a certain mass of deionized water in a certain proportion, rapidly stirring for a certain period of time, centrifuging and filtering the black matter, washing it with deionized water for 3-5 times, and drying it in an oven for a certain period of time to obtain a magnetic coal gasification slag composite material precursor;
[0010] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to a certain calcination temperature at a certain heating rate under a N2 atmosphere, and then calcined for a certain time to obtain a magnetic coal gasification slag composite material.
[0011] Preferably, in step (1), the ball-to-material mass ratio is (5-40):1, and the ball milling time is 10-60 min.
[0012] Preferably, in step (2), the mass ratio of the complexing agent, which is an organic compound containing polyphenol hydroxyl or carboxyl, to the ball-milled coal gasification slag is (1-5):1, the mass ratio of the ball-milled coal gasification slag to deionized water is 1:(50-100), the stirring reaction time is 5-60 min, and the vacuum drying time is 5-12 h.
[0013] Preferably, the complexing agent in step (2) includes but is not limited to tannic acid, ethylenediaminetetraacetic acid and citric acid.
[0014] Preferably, in step (3), the heating rate is 2-5°C / min, the calcination temperature is 500-1000°C, and the calcination time is 0.5-3h.
[0015] Preferably, the exposed metals in step (1) include but are not limited to Fe and Mn.
[0016] The present invention also provides an application of a mechanochemical method for preparing a magnetic coal gasification slag composite material, wherein the magnetic coal gasification slag composite material is used for catalytic degradation of organic pollutants in water, and the degradation operation steps are: adding a certain amount of the magnetic coal gasification slag composite material and peroxymonosulfate together into phenol-containing wastewater, and stirring at room temperature for 30-60 minutes.
[0017] Preferably, 0.2-1.0 g of the magnetic coal gasification slag composite material is added to each liter of the phenol-containing wastewater; and 1-4 mmol of permonosulfate is added to each liter of the phenol-containing wastewater.
[0018] Preferably, the organic pollutants in each liter of the phenol-containing wastewater include but are not limited to 50 mg of bisphenol A or phenol, and the removal efficiency of organic pollutants is 99.0-100%.
[0019] Working principle of the present invention: The present invention uses coal gasification slag as raw material, and crushes the silicon-aluminum minerals in the coal gasification slag in a short-time and high-speed environment through mechanical high-energy ball milling, so as to fully expose more active metals (such as Fe and Mn) wrapped by silicon-aluminum minerals. Then, the migration and aggregation of metals to the outside are promoted through the chelation action of the chelating agent, and the metal activity is stimulated in the N2 roasting environment to form new metal active sites, which is beneficial to the activation of PMS during the reaction process and improves the degradation efficiency of organic pollutants in water. Therefore, the present application uses a mechanochemical method to promote the exposure and migration and transformation of metal substances in coal gasification slag, and obtains a magnetic coal gasification slag composite material in which endogenous metals are exposed and migrated to the outer layer of silicon-aluminum minerals or residual carbon, thereby realizing the reconstruction and reuse of endogenous metals in coal gasification slag.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention uses coal gasification slag as raw material, which has a wide source, huge output, low price and is easy to obtain. The preparation process of the magnetic coal gasification slag composite material is simple and environmentally friendly, and no waste acid or waste alkali is generated, providing a new method for large-scale utilization of coal gasification slag.
[0022] (2) In the preparation process of the magnetic composite material of the present invention, the application of the mechanical high-energy ball milling method can not only realize the treatment of coal gasification slag, but also quickly achieve the purpose of crushing the silicon-aluminum minerals in the coal gasification slag in a short time, so that the metal wrapped by the silicon-aluminum minerals is exposed over a large area, thereby improving the deconstruction and utilization efficiency of endogenous metals.
[0023] (3) In the preparation process of the magnetic composite material, the present invention promotes the migration and transformation of endogenous metals in the coal gasification slag from being wrapped in the silicon-aluminum mineral to being exposed and then fixed in the outer layer through the complexation of the complexing agent with the exposed metals in the ball-milled coal gasification slag, especially the exposure of metal Fe in the coal gasification slag. This not only makes the coal gasification slag composite material have a certain magnetic property, but also provides more active sites, thereby achieving the purpose of migration, transformation and recycling of endogenous metals in the coal gasification slag in the system, and reducing the cost of adding active metals in the preparation process.
[0024] (4) The magnetic coal gasification slag composite material prepared by the present invention has a strong catalytic activity for PMS, and can efficiently catalytically degrade organic pollutants in water, with a degradation efficiency of 99-100%. At the same time, because of the phase transformation process during the preparation process, the obtained coal gasification slag composite material has a certain magnetic property, which is easy to separate and recycle in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The SEM and EDS spectra of the raw coal gasification slag, ball-milled coal gasification slag and magnetic coal gasification slag composite material in Example 2 of the present invention are shown in FIG. 2, wherein: (a) the SEM spectra and EDS spectra of the raw coal gasification slag in Example 2; (b) the SEM spectra and EDS spectra of the ball-milled coal gasification slag in Example 2; (c) the SEM spectra and EDS spectra of the magnetic coal gasification slag composite material in Example 2;
[0026] Figure 2 This is the X-ray diffraction spectrum (XRD) of the raw coal gasification slag, the ball-milled coal gasification slag and the magnetic coal gasification slag composite material in Example 2 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention easier to understand, the technical solution of the present invention is now clearly and completely described in the form of specific embodiments in conjunction with the accompanying drawings.
[0028] Embodiment 1:
[0029] The method for preparing the magnetic coal gasification slag composite material by the mechanochemical method of this embodiment comprises the following steps:
[0030] (1) 1 g of coal gasification slag is loaded into a ball milling tank of a high-energy ball mill together with grinding balls at a ball-to-material mass ratio of 5:1, and the ball milling is performed at a rotation speed of 2000 r / min for 20 min to fully expose the endogenous metals in the coal gasification slag, thereby obtaining ball-milled coal gasification slag with exposed metals;
[0031] (2) adding tannic acid as a complexing agent and the ball-milled coal gasification slag obtained in step (1) into deionized water in a mass ratio of 1:1, wherein the mass ratio of the ball-milled coal gasification slag to deionized water is 1:50, and after rapid stirring for 10 minutes, centrifuging and filtering the black substance, washing it with deionized water for 3 times, and drying it in an oven for 10 hours, to obtain a magnetic coal gasification slag composite material precursor;
[0032] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to 1000° C. in a N 2 atmosphere at a heating rate of 2° C. / min and calcined for 0.5 h to obtain a magnetic coal gasification slag composite material.
[0033] The magnetic coal gasification slag composite material was used in an experiment to catalyze the degradation of organic pollutants in water. The specific steps were as follows: 0.2 g of the magnetic coal gasification slag composite material and 4 mmol PMS were added to 1 L of phenolic wastewater containing 50 mg bisphenol A, and stirred at room temperature for 50 minutes. The degradation efficiency of bisphenol A was 99.0%.
[0034] Embodiment 2:
[0035] The method for preparing the magnetic coal gasification slag composite material by the mechanochemical method of this embodiment comprises the following steps:
[0036] (1) 2 g of coal gasification slag was loaded into a ball milling tank of a high-energy ball mill together with grinding balls at a ball-to-material mass ratio of 10:1, and the ball milling was performed at a rotation speed of 2000 r / min for 30 min to fully expose the endogenous metals in the coal gasification slag, thereby obtaining ball-milled coal gasification slag with exposed metals;
[0037] (2) adding tannic acid as a complexing agent and the ball-milled coal gasification slag obtained in step (1) into deionized water in a mass ratio of 2:1, wherein the mass ratio of the ball-milled coal gasification slag to deionized water is 1:80, and after rapid stirring for 10 minutes, centrifuging and filtering the black substance, washing it with deionized water for 5 times, and drying it in an oven for 12 hours, to obtain a magnetic coal gasification slag composite material precursor;
[0038] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to 800° C. in a N2 atmosphere at a heating rate of 5° C. / min and calcined for 2 h to obtain a magnetic coal gasification slag composite material.
[0039] The magnetic coal gasification slag composite material was used in an experiment to catalyze the degradation of organic pollutants in water. The specific steps were as follows: 0.6 g of the magnetic coal gasification slag composite material and 2 mmol of PMS were added to 1 L of phenolic wastewater containing 50 mg of bisphenol A, and stirred at room temperature for 60 minutes. The degradation efficiency of bisphenol A was 100%.
[0040] Embodiment 3:
[0041] The method for preparing the magnetic coal gasification slag composite material by the mechanochemical method of this embodiment comprises the following steps:
[0042] (1) 5 g of coal gasification slag was loaded into a ball milling tank of a high-energy ball mill together with grinding balls at a ball-to-material mass ratio of 40:1, and the ball milling was performed at a rotation speed of 2000 r / min for 60 min to fully expose the endogenous metals in the coal gasification slag, thereby obtaining ball-milled coal gasification slag with exposed metals;
[0043] (2) adding citric acid as a complexing agent and the ball-milled coal gasification slag obtained in step (1) into deionized water in a mass ratio of 5:1, wherein the mass ratio of the ball-milled coal gasification slag to deionized water is 1:100, and after rapid stirring for 60 minutes, centrifuging and filtering the black substance, washing it with deionized water for 4 times, and drying it in an oven for 5 hours, to obtain a magnetic coal gasification slag composite material precursor;
[0044] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to 500° C. in a N2 atmosphere at a heating rate of 5° C. / min and calcined for 3 h to obtain a magnetic coal gasification slag composite material.
[0045] The magnetic coal gasification slag composite material was used in an experiment to catalyze the degradation of organic pollutants in water. The specific steps were as follows: 1g of the magnetic coal gasification slag composite material and 1mmol of PMS were added to 1L of phenol-containing wastewater containing 50mg of phenol, and stirred at room temperature for 30 minutes. The degradation efficiency of phenol was 99.7%.
[0046] Embodiment 4:
[0047] The method for preparing the magnetic coal gasification slag composite material by the mechanochemical method of this embodiment comprises the following steps:
[0048] (1) 3 g of coal gasification slag was loaded into a ball milling tank of a high-energy ball mill together with grinding balls at a ball-to-material mass ratio of 25:1, and the ball milling was performed at a rotation speed of 2000 r / min for 40 min to fully expose the endogenous metals in the coal gasification slag, thereby obtaining ball-milled coal gasification slag with exposed metals;
[0049] (2) adding a complexing agent, ethylenediaminetetraacetic acid, and the ball-milled coal gasification slag obtained in step (1) into deionized water in a mass ratio of 3:1, wherein the mass ratio of the ball-milled coal gasification slag to deionized water is 1:75, and rapidly stirring for 20 minutes, centrifuging and filtering the black substance, washing it with deionized water for 3 times, and drying it in an oven for 9 hours to obtain a magnetic coal gasification slag composite material precursor;
[0050] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to 800° C. in a N 2 atmosphere at a heating rate of 3° C. / min and calcined for 1.5 h to obtain a magnetic coal gasification slag composite material.
[0051] The magnetic coal gasification slag composite material was used in an experiment to catalyze the degradation of organic pollutants in water. The specific steps were as follows: 0.7 g of the magnetic coal gasification slag composite material and 2.5 mmol PMS were added to 1 L of phenol-containing wastewater containing 50 mg phenol, and stirred at room temperature for 60 minutes. The degradation efficiency of phenol was 99.9%.
[0052] Embodiment 5:
[0053] The method for preparing the magnetic coal gasification slag composite material by the mechanochemical method of this embodiment comprises the following steps:
[0054] (1) 1.5 g of coal gasification slag was loaded into a ball milling tank of a high-energy ball mill together with grinding balls at a ball-to-material mass ratio of 15:1, and the ball milling was performed at a rotation speed of 2000 r / min for 10 min to fully expose the endogenous metals in the coal gasification slag, thereby obtaining ball-milled coal gasification slag with exposed metals;
[0055] (2) adding tannic acid as a complexing agent and the ball-milled coal gasification slag obtained in step (1) to deionized water in a mass ratio of 4:1, wherein the mass ratio of the ball-milled coal gasification slag to deionized water is 1:90, and after rapid stirring for 5 minutes, centrifuging and filtering the black substance, washing it with deionized water for 5 times, and drying it in an oven for 8 hours, to obtain a magnetic coal gasification slag composite material precursor;
[0056] (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to 900° C. in a N2 atmosphere at a heating rate of 5° C. / min and calcined for 2 h to obtain a magnetic coal gasification slag composite material.
[0057] The magnetic coal gasification slag composite material was used in an experiment to catalyze the degradation of organic pollutants in water. The specific steps were as follows: 0.8 g of the magnetic coal gasification slag composite material and 1.5 mmol PMS were added to 1 L of phenolic wastewater containing 50 mg bisphenol A, and stirred at room temperature for 60 minutes. The degradation efficiency of bisphenol A was 99.8%.
[0058] Figure 1 The SEM and EDS spectra of the raw coal gasification slag, ball-milled coal gasification slag and magnetic coal gasification slag composite material in Example 2 of the present invention are shown in Figure 2, including: (a) SEM spectra and EDS spectra of the raw coal gasification slag in Example 2; (b) SEM spectra and EDS spectra of ball-milled coal gasification slag in Example 2; (c) SEM spectra and EDS spectra of the magnetic coal gasification slag composite material in Example 2. Figure 1 It can be seen that the iron element is mainly concentrated on the silica-alumina minerals. Compared with the raw coal gasification slag, the iron element in the ball-milled coal gasification slag is more concentrated, mainly because the ball milling breaks the silica-alumina minerals and fully exposes the metal elements wrapped by the silica-alumina minerals. After complexation and roasting, the iron species of the obtained magnetic coal gasification slag composite material have agglomeration phenomenon, mainly because the addition of tannic acid promotes the concentration of exposed metals, thereby realizing the process of endogenous metals in coal gasification slag from wrapping to exposure and then aggregation.
[0059] Figure 2 The X-ray diffraction spectra (XRD) of the raw coal gasification slag, ball-milled coal gasification slag and magnetic coal gasification slag composite material in Example 2 of the present invention are shown in FIG. Figure 2 It can be seen that compared with the raw coal gasification slag, the XRD of ball-milled coal gasification slag has no obvious phase change, indicating that the ball milling process has not changed the phase composition of the material. After complexation and calcination, the obtained magnetic coal gasification slag composite material shows characteristic peaks of elemental iron and Fe3O4, indicating that the iron species exposed by ball milling are complexed and aggregated in the chemical method, and the migration and reconstruction of iron elements are achieved through calcination to form a new phase.
[0060] It can be seen that in the present invention, the silicon-aluminum minerals in the coal gasification slag are broken by mechanical high-energy ball milling, so that more active metals (such as Fe and Mn) wrapped by the silicon-aluminum minerals can be fully exposed. The complexing action of the complexing agent can promote the migration and aggregation of metals to the outside, and stimulate the activity of metals in the N2 roasting environment to form new metal active sites, which is beneficial to the activation of PMS in the reaction process and improves the degradation efficiency of organic pollutants in water.
[0061] It should be noted that the embodiments described herein are only partial embodiments of the present invention, rather than all implementations of the present invention, and the embodiments are only exemplary, and their role is only to provide a more intuitive and clear way to understand the content of the present invention, rather than to limit the technical solutions described in the present invention. Without departing from the concept of the present invention, all other implementation methods that can be thought of by ordinary technicians in this field without creative work, and other simple replacements and various changes to the technical solutions of the present invention, all belong to the protection scope of the present invention.
Claims
1. A method for preparing a magnetic coal gasification slag composite material by a mechanochemical method, characterized in that: The following steps are involved: (1) a certain mass of coal gasification slag is loaded into a ball milling tank of a high energy ball mill together with grinding balls according to a certain ball-to-material mass ratio, and ball milled at a speed of 2000 r / min for a certain period of time to obtain ball-milled coal gasification slag with exposed metal; (2) adding the complexing agent and the ball-milled coal gasification slag obtained in step (1) to a certain mass of deionized water in a certain proportion, rapidly stirring for a certain period of time, centrifuging and filtering the black matter, washing it with deionized water for 3-5 times, and drying it in an oven for a certain period of time to obtain a magnetic coal gasification slag composite material precursor; (3) The magnetic coal gasification slag composite material precursor obtained in step (2) is heated to a certain calcination temperature at a certain heating rate under a N2 atmosphere, and then calcined for a certain time to obtain a magnetic coal gasification slag composite material.
2. The method for preparing a magnetic coal gasification slag composite material by a mechanochemical method according to claim 1, characterized in that: In the step (1), the ball-to-material mass ratio is (5-40):1, and the ball milling time is 10-60 min.
3. The method for preparing a magnetic coal gasification slag composite material by a mechanochemical method according to claim 1, characterized in that: In the step (2), the complexing agent is an organic compound containing polyphenolic hydroxyl or carboxyl groups, the mass ratio of the complexing agent to the ball-milled coal gasification slag is (1-5):1, the mass ratio of the ball-milled coal gasification slag to deionized water is 1:(50-100), the stirring reaction time is 5-60 minutes, and the vacuum drying time is 5-12 hours.
4. The method for preparing a magnetic coal gasification slag composite material by a mechanochemical method according to claim 1, characterized in that: The complexing agent in step (2) includes but is not limited to tannic acid, ethylenediaminetetraacetic acid and citric acid.
5. The method for preparing a magnetic coal gasification slag composite material by a mechanochemical method according to claim 1, characterized in that: In the step (3), the heating rate is 2-5°C / min, the calcination temperature is 500-1000°C, and the calcination time is 0.5-3h.
6. The method for preparing a magnetic coal gasification slag composite material by a mechanochemical method according to claim 1, characterized in that: The exposed metals in step (1) include but are not limited to Fe and Mn.
7. The use of the mechanochemical method for preparing magnetic coal gasification slag composite material according to claim 1, characterized in that: The magnetic coal gasification slag composite material is prepared by any one of claims 1 to 6, and the magnetic coal gasification slag composite material is used for catalytic degradation of organic pollutants in water, and the degradation operation steps are: adding a certain amount of the magnetic coal gasification slag composite material and peroxymonosulfate together into phenol-containing wastewater, and stirring at room temperature for 30-60 minutes.
8. The use of the mechanochemical method for preparing a magnetic coal gasification slag composite material as claimed in claim 7, characterized in that: 0.2-1.0 g of magnetic coal gasification slag composite material is added per liter of the phenol-containing wastewater; and 1-4 mmol of permonosulfate is added per liter of the phenol-containing wastewater.
9. The use of the mechanochemical method for preparing a magnetic coal gasification slag composite material as claimed in claim 7, characterized in that: The organic pollutants in each liter of the phenol-containing wastewater include, but are not limited to, 50 mg of bisphenol A or phenol, and the removal efficiency of the organic pollutants is 99.0-100%.